Genome-wide association study between copy number variation regions and carcass- and meat-quality traits in Nellore cattle - Berton, Mariana Piatto [UNESP]; Antunes Lemos, Marcos Vinicius de [UNESP]; Seleguim Chud, Tatiane Cristina; Bonvino Stafuzza, Nedenia [UNESP]; Kluska, Sabrina [UNESP]; Amorim, Sabrina Thaise [UNESP]; Silva Ferlin Lopes, Lucas [UNESP]; Cravo Pereira, Angelica Simone; Bickhart, Derek; Liu, George; Galvao de Albuquerque, Lucia [UNESP]; Baldi, Fernando [UNESP] (Csiro Publishing, 2021)
Context. Indicine breeds are the main source of beef products in tropical and subtropical regions. However, genetic improvement for carcass- and meat-quality traits in zebu cattle have been limited and genomics studies concerning structural variations that influence these traits are essential. Aim. The aim of this study was to perform a genome-wide association study between copy number variation regions (CNVRs) and carcass- and meat quality-traits in Nellore cattle. Methods. In total, 3794 animals, males and females included, were genotyped using a 777 962 single-nucleotide polymorphism platform of BovineHD BeadChip (777k; Illumina Inc.). Of these, 1751 Nellore bulls were slaughtered at 24 months of age for further carcass beef analysis. The following traits were studied: beef tenderness, marbling, rib-eye area, backfat thickness and meat colour (lightness, redness and yellowness). The CNV detection was conducted through PennCNV software. The association analyses were performed using CNVRuler software. Key results. Several identified genomic regions were linked to quantitative trait loci associated with fat deposition (FABP7) and lipid metabolism (PPARA; PLA2 family; BCHE), extracellular matrix (INS; COL10A1), contraction (SLC34A3; TRDN) and muscle development (CAPZP). The gene-enrichment analyses highlighted biological mechanisms directly related to the metabolism and synthesis of lipids and fatty acids. Conclusions. The large number of potential candidate genes identified within the CNVRs, as well as the functions and pathways identified, should help better elucidate the genetic mechanisms involved in the expression of beef and carcass traits in Nellore cattle. Several CNVRs harboured genes that might have a functional impact to improve the beef and carcass traits. Implications. The results obtained contribute to upgrade the sensorial and organoleptic attributes of Nellore cattle and make feasible the genetic improvement of carcass- and meat-quality traits.
Keywords: beef cattle; Bos indicus; meat quality traits; carcass composition; genomics